Field test of a silicon carbide metro propulsion system with reduced losses and acoustic noise - Martin Lindahl; Torbjörn Trostén; Daniel Jansson; Mikael H Johansson; Erik Velander; Anders Blomberg; Hans‐Peter Nee (IET Electrical Systems in Transportation)
Abstract Results are reported from a successful field test with a silicon carbide (SiC) metal‐oxide‐semiconductor field‐effect transistor (MOSFET) traction inverter. The train has been operated over a 3‐month period in the Stockholm metro system. Increased traction inverter power density has been achieved, with volume and weight reductions of 51% and 25%, respectively. Lower power losses permit the use of car motion cooling. A sound pressure level reduction of 9 dB(A) was measured in the field with the higher inverter switching frequency permitted by using SiC. Complementing tests have been performed in the laboratory to compare thermal performance of silicon and SiC in the same power semiconductor housing. Propulsion system power losses are reduced by 19% with SiC. Acoustic noise reductions while increasing switching frequency are also reported.